Instagram reels as a medium of transcultural interaction: A netnographic study of wedding, humor, and diaspora family content - Indah Tjahjawulan; Iwan Gunawan (Universitas Indraprasta PGRI, 2026)
In the context of globalization, cultural practices and ideologies are increasingly shaped through processes of borrowing, mixing, and remaking, resulting in new hybrid cultural forms. This article examines Instagram Reels as a medium of transcultural interaction by focusing on selected user-generated content related to wedding ceremonies, pre-wedding photo shoots, humor scenes, and slice-of-life narratives of diaspora families or international couples. Using a qualitative netnographic approach, the study selected 15 publicly accessible Reels and analyzed their visual elements, sound, narration, language use, symbolic references, and cultural markers. The findings show that Instagram Reels functions not only as a short-video platform for self-expression and entertainment, but also as a participatory space where local traditions, global popular culture, and everyday intercultural practices are remixed. Through these interactions, influencers and ordinary users produce hybrid cultural expressions that circulate beyond geographical and national boundaries. The study contributes to the understanding of digital platforms as fluid spaces of transcultural dialogue, where culture is continuously negotiated, reproduced, and recontextualized through user participation.